MENOPAUSAL SYMPTOMS AND FISH CONSUMPTION OF MENOPAUSAL WOMEN IN THE COASTAL AREAS OF SOUTHEAST SULAWESI, INDONESIA - Juminten Saimin; Steven Ridwan; Mono Valentino Yohanis; Lianawati Lianawati; Arimaswati Arimaswati; Hamliati Hamliati (Public Health of Indonesia)
Background: Menopausal symptoms are common problem in menopausal women. The severity of menopausal symptoms is influenced by the interaction of biological, genetic and nutritional factors.